Pengembangan PDPT Berbasis Framework Dengan Teknologi Web Service SOAP dan REST di Universitas Semarang - Whisnumurti Adhiwibowo; Galet Guntoro Setiaji; Tirta Jurista Kumkamdhani (Universitas PGRI Semarang, 2019)
One indication of the development of a tertiary institution can be seen from the number of students applying from year to year. The increasing number of students is an identification that the tertiary institution is in high demand by the community. University student data is stored in a university database or often called PDPT. PDPT data is used for various things, such as calculating the ratio of lecturers and students, calculating the number of graduations, calculating class ratios to university income. Because of the importance of the PDPT data, the validity of the PDPT data must be maintained. The problem that arises at the University of Semarang is that the data is only contained in the central server and is not distributed well globally or in detail up to the Study Program and the Quality Assurance Agency. This requires an alternative way to validate student data so that student data can be monitored continuously. The method can be done by using software development methods using a framework. Data obtained through the computer center by utilizing a web service so that data can be retrieved directly.